Materials Suitable for Osteochondral Regeneration - Novotná, Renáta; Franková, Jana (ACS omega, 2024)
Osteochondral defects affect articular cartilage, calcified cartilage, and subchondral bone. The main problem that they cause is a different behavior of cell tissue in the osteochondral and bone part. Articular cartilage is composed mainly of collagen II, glycosaminoglycan (GAG), and water, and has a low healing ability due to a lack of vascularization. However, bone tissue is composed of collagen I, proteoglycans, and inorganic composites such as hydroxyapatite. Due to the discrepancy between the characters of these two parts, it is difficult to find materials that will meet all the structural and other requirements for effective regeneration. When designing a scaffold for an osteochondral defect, a variety of materials are available, e.g., polymers (synthetic and natural), inorganic particles, and extracellular matrix (ECM) components. All of them require the accurate characterization of the prepared materials and a number of in vitro and in vivo tests before they are applied to patients. Taken in concert, the final material needs to mimic the structural, morphological, chemical, and cellular demands of the native tissue. In this review, we present an overview of the structure and composition of the osteochondral part, especially synthetic materials with additives appropriate for healing osteochondral defects. Finally, we summarize in vitro and in vivo methods suitable for evaluating materials for restoring osteochondral defects.